2012
DOI: 10.1167/iovs.11-8802
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Suppression of Dendritic Cell Function Helps Maintain Immune Regulation in the Eye during Human Uveitis

Abstract: These data indicate that the ocular microenvironment continues to regulate DC function during uveitis, despite IFNγ-driven upregulation of MHC expression, supporting the hypothesis that immune regulation within the eye is maintained during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…Hence, DCs not only are crucial for inducing primary immune responses, but also may be relevant for generating immunological tolerance and for the regulation of the T-cell-mediated immune response type [ 18 , 38 ]. Thus, during human uveitis, the aqueous humor suppression of DCs helps maintain immune regulation in the eye [ 39 ].…”
Section: Monocytes Macrophages and Dendritic Cells In The Eyementioning
confidence: 99%
“…Hence, DCs not only are crucial for inducing primary immune responses, but also may be relevant for generating immunological tolerance and for the regulation of the T-cell-mediated immune response type [ 18 , 38 ]. Thus, during human uveitis, the aqueous humor suppression of DCs helps maintain immune regulation in the eye [ 39 ].…”
Section: Monocytes Macrophages and Dendritic Cells In The Eyementioning
confidence: 99%
“…Blood DCs contain three subsets: CD1c + (BDCA1) myeloid dendritic cell 1 (mDC1), CD141 + (BDCA3) myeloid dendritic cell 2 (mDC2), and CD303 + (BDCA2) plasmacytoid DCs (pDCs) [9], which are from Lineage 1 − (Lin1, including CD3, CD14, CD16, CD19, CD20 and CD56) HLADR + cells. Myeloid DCs actively infiltrate into the eye and can be seen suspending in the aqueous humor of uveitis patients [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Denniston et al used human MoDCs as a model to test the effects of non-inflammatory and inflammatory AqH supernatant, noting that exposure of MoDCs from healthy controls to uveitic AqH from patients with active inflammation induced upregulation of MHC I and II and reduced CD86. Interestingly these changes were characteristic of the mDCs that had been directly isolated from these uveitis patients, providing evidence for the potential role of the ocular microenvironment in DC regulation, maturation and function 15; 16 .…”
Section: Abnormalities Of Dendritic Cell Subsets In Non-infectiousmentioning
confidence: 83%
“…This may be particularly relevant to those forms of uveitis that have a proposed association with gram negative bacteria such as HLA-B27 associated anterior uveitis 5 . Denniston et al reported that mDCs isolated from human uveitic aqueous humor (AqH) were characterized by elevated MHC I and II, but reduced CD86 compared with matched peripheral blood mDCs 16 .…”
Section: Abnormalities Of Dendritic Cell Subsets In Non-infectiousmentioning
confidence: 99%